Role of digital health technologies in improving health financing and universal health coverage in Sub-Saharan Africa: a comprehensive narrative review - Awosiku, Olutola Vivian; Gbemisola, Ibrahim Nafisa; Oyediran, Oluwafiponmile Thomas; Egbewande, Oluwaseyi Muyiwa; Lami, Jibril Habibah; Afolabi, Daniel; Okereke, Melody; Effiong, Fortune (Frontiers in Digital Health, 2025)
Digital technologies play a key role in developing a comprehensive and resilient healthcare delivery system in many low and middle-income countries in Sub-Saharan Africa. These technologies aim not only to address the financial accessibility gap for health needs but also to enhance innovation, partnerships, data management, and performance across healthcare stakeholders. By bridging gaps in access and reducing inequities, digital health technologies have the potential to mitigate socioeconomic disparities in healthcare delivery, particularly in resource-limited settings. This paper explores existing data on health challenges, financing, and universal health coverage in sub-Saharan Africa, along with examining digital health technologies, their adoption, and implementation. Case studies from initiatives such as M-TIBA in Kenya, JAMII in Tanzania, and L'UNION TECHNIQUE DE LA MUTUALITÉ MALIENNE in Mali are presented, along with recommendations for scale-up, policy enhancement, collaboration, support, and identification of research gaps and areas for further exploration.